PENGARUH PENGGUNAAN KERTAS KOKORU TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN DI TK SYAKHSHIYATUL UMMAH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Sari, Dewi Novila Sari Novila; Puspitasari, Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the influence of the use of color corrugated paper about the creativity of children aged 5-6 year in kindergarten syakhshiatul ummah  siak hulu kabupaten kampar . This type of research is experimental design with one group pretest posttest design. Population and sample in this study were 20 children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu Kabupaten Kampar. Collection techniques namely direct observation of children's activities. Data were analyzed using t test formula and method of statistical analysis with SPSS for windows release.17. The hypothesis of this study was the effect of the use of paper kokoru to the creativity of children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu Kabupaten Kampar. It can be seen from the analysis of data obtained t value amounted to 18,293, while t table with level sig (5%) and (df = n - 1 = 20-1 = 19) the value of t table of 2,093. Because t is greater than t table or 18,293 > 2,093, it means that the effect of the use of paper kokoru against the creativity of children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu Kabupaten Kampar. Determinant coefficient generated is equal to r2 = 0,648. This means that the effect of the use of paper kokoru against the creativity of children in kindergarten Syakhshiatul Ummah by 64,8%. And can researchers conclude that the presence of the effect of the use of paper kokoru against the creativity of children in kindergarten Syakhshiatul Ummah Siak Hulu Kabupaten Kampar . The keywords: Color corrugated paper , Creativity